Development of Rhino-Themed Mobile Learning for Critical Thinking Skills of Ecosystem Concepts for 5th Grade Students - Ulinuha, Widda; Leksono, Suroso Mukti; Nulhakim, Lukman (International Journal of Biology Education Towards Sustainable Development, 2025)
Learning media plays an important role in supporting the success of the learning process, especially in developing students' critical thinking skills. This study aimed to develop mobile learning media with the theme of the One-Horned Rhinoceros, an endemic animal typical of Ujung Kulon National Park, as a contextual learning tool to improve elementary school students' critical thinking skills in ecosystem material. The method used is Research and Development (RD) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The study results showed that the media was developed to analyze student needs and local context through an interactive design process, expert validation, and classroom trials and evaluations. The validation results showed a feasibility level of 91% (very good category). The effectiveness of the media is reflected in the N-Gain value of 0.7171 (high category). The responses of teachers and students to the media were also very positive, 87% and 98.7% respectively. In conclusion, the product developed is feasible and effective and can improve students' critical thinking skills.